Quality of life of transsexuals after sex reassignment surgery (Research, Society and Development, 2022)
This study aimed to identify the benefits and post-surgical difficulties related to the quality of life of transsexual people after sex reassignment surgery. This is an integrative review, carried out between April and June 2021. Articles were collected in the following databases: Virtual Health Library (VHL), MEDLINE, Scientific Electronic Library Online (SciELO) and PubMed. This search provided the selection of 12 articles, published between 2015 and 2020. After reading and analyzing the objectives and results of these works, it was possible to group them according to similarities, enabling the creation of four strands. They are: scarcity of instruments to calculate quality of life; Post-surgical complications; Importance of multidisciplinary monitoring before and after surgery; Quality of life/satisfaction after the surgical procedure. In general, even with some postoperative complications, studies have shown that the surgical procedure has positive effects on the patient's life, especially indicating a high satisfaction for aesthetic and psychosocial issues after the procedure. However, many patients reported inadequate and scarce post-surgery multidisciplinary follow-up. Therefore, it is concluded that there are few instruments to assess the quality of life of transsexual people. In addition, multiprofessional follow-up is extremely important in the pre- and post-surgical period to avoid possible complications.